Removal of endrin and dieldrin isomeric pesticides through stereoselective adsorption behavior on the graphene oxide-magnetic nanoparticles - Shrivas, K.; Ghosale, A.; Nirmalkar, N.; Srivastava, A; Singh, S. K.; Shinde, S. S. (Environmental Science and Pollution Research, 2017)
A novel stereoselective removal behavior of isomeric endrin and dieldrin pesticides from sample solution is demonstrated using nanocomposite of graphene oxide (GO) and iron oxide (Fe3O4) magnetic nanoparticles (MNPs). The removal efficiency of endrin and dieldrin was found higher when GO-MNPs was used as a separating probe than the individual use of GO and MNPs. The removal efficiency of both the pesticides was found to be more favorable when the dosage amount of GO-MNPs was 30 mg for 30-min contact time with pH 4.0 at room temperature. The good correlation of determination (R2) with 0.975 and 0.973 values obtained for endrin and dieldrin, respectively demonstrated a well fitting of Langmuir adsorption isotherm model. The higher removal percentage (86.0%) and higher slope value of Langmuir adsorption isotherm were estimated for endrin compared to dieldrin (74.0%). The reason for higher adsorption percentage of endrin is due to the endo-position of oxygen atom in molecule favors more interaction of molecules with GO-MNPs compared to the exo-position of oxygen present in dieldrin. In addition, the higher value of R2 for endrin and dieldrin demonstrated better suitability of pseudo-first-order and pseudo-second-order kinetic models, respectively. The advantages of the present method are use of simple UV-vis spectrophotometry for monitoring and low-cost use of GO-MNPs nanomaterial for the removal of pesticides from sample solution. © 2017 Springer-Verlag GmbH Germany
Keywords: Dieldrin; Endrin; Isomeric Pesticides; Removal